Reading English-Language Haiku: Processes of Meaning Construction Revealed by Eye Movements - Hermann J Mueller; Thomas Geyer; Franziska Günther; Jim Kacian; Stella Pierides (Bern Open Publishing, 2017)
In the present study, poets and cognitive scientists came together to investigate the construction of meaning in the process of reading normative, 3-line English-language haiku (ELH), as found in leading ELH journals. The particular haiku which we presented to our readers consisted of two semantically separable parts, or images, that were set in a 'tense' relationship by the poet. In our sample of poems, the division, or cut, between the two parts was positioned either after line 1 or after line 2; and the images related to each other in terms of either a context-action association (context-action haiku) or a conceptually more abstract association (juxtaposition haiku). From a constructivist perspective, understanding such haiku would require the reader to integrate these parts into a coherent 'meaning Gestalt', mentally (re-)creating the pattern intended by the poet (or one from within the poem's meaning potential). To examine this process, we recorded readers' eye movements, and we obtained measures of memory for the read poems as well as subjective ratings of comprehension difficulty and understanding achieved. The results indicate that processes of meaning construction are reflected in patterns of eye movements during reading (1st-pass) and re-reading (2nd- and 3rd-pass). From those, the position of the cut (after line 1 vs. after line 2) and, to some extent, the type of haiku (context-action vs. juxtaposition) can be 'recovered'. Moreover, post-reading, readers tended to explicitly recognize a particular haiku they had read if they had been able to understand the poem, pointing to a role of actually resolving the haiku's meaning (rather than just attempting to resolve it) for memory consolidation and subsequent retrieval. Taken together, these first findings are promising, suggesting that haiku can be a paradigmatic material for studying meaning construction during poetry reading.